Genetic diversity and expression profiles of cysteine phytases in the sheep rumen during a feeding cycle. (13th October 2014) - Li, Z.; Huang, H.; Zhao, H.; Meng, K.; Zhao, J.; Shi, P.; Yang, P.; Luo, H.; Wang, Y.; Yao, B.
Abstract Cysteine phytase is the main phytate‐degrading enzyme of ruminant animals. To explore the genetic diversity and dynamic expression profile of cysteine phytase in sheep rumen during a feeding cycle, four transcript (0, 4, 9 and 16 h after feeding) and one DNA (9 h after feeding) clone libraries were constructed, respectively. A total of 46 distinct gene fragments were identified, and most of these sequences had low identities (<60%) with known phytases. Great divergence was found in the constitution and abundance of genes at the genome and transcriptional levels, and the transcript data are more reliable to reflect the information of functional genes. Phylogenetic analysis indicated that the genes from uncultured bacteria instead of Firmicutes played the major phytate‐degrading role. Further comparative analysis revealed the dynamic constitution of cysteine phytase genes in rumen at different time points. Significance and Impact of the Study Ruminal phytases, that are cysteine phytases, are novel in sequences and functions. Great divergence in the constitution and abundance of cysteine phytase genes at the genome and transcriptional levels suggested that transcript data are more reliable to reflect the information of functional genes. Phylogenetic and rarefaction analyses indicated that the cysteine phytase genes from uncultured bacteria instead of Firmicutes play the major phytate‐degrading role in rumen, and their constitution is dynamic at different time points. This study provides a new insight into ruminal cysteine phytase genes and undermines their expression profiles over a whole feeding cycle.